Self-reference by politicians on Twitter: Strategies to adapt to 140 characters - Coesemans, Roel; De Cock, Barbara (Journal of pragmatics, 2017)
•Spanish and Belgian European election candidates tweet mainly for self-promotion.•Via conciseness strategies politicians adapt to technological constraints of Twitter.•These conciseness strategies depend on language-specific features.•Personal branding is also achieved by exploiting Twitter handles and hashtags.•Third person and creative self-references indicate metapragmatic awareness. This paper studies how language is used on Twitter by Belgian and Spanish politicians in the context of the 2014 European elections campaign. Taking a pragmatic perspective on language use, we investigate three interrelated aspects of political communication on Twitter: (i) how political candidates adapt their language to the technological affordances of Twitter; (ii) which linguistic strategies the politicians use to express self-reference in function of different communicative goals and in relation to contextual factors such as ideological profile or nationality; and (iii) how some of the image building and community building strategies can be interpreted as reflexive signs of metapragmatic awareness. This study shows that the practice of self-referencing is a prominent feature of politicians’ discourse on Twitter, which is used as a tool for professional communication, as most of the self-references refer to professional rather than private identities. When spreading tweets, the studied Belgian and Spanish politicians use a number of adaptability strategies. They use conciseness strategies, such as subject pronoun ellipsis in Dutch and full subject NP constructions of a first person plural verb form in Spanish and Catalan, to accommodate to the 140 character constraint of the microblogging service. To express identities the politicians not only make use of first person pronouns, but also use the Twitter handle, the hashtag or proper nouns, referring to themselves in the third person. This practice shows that Twitter is not only a tool for professional political communication, but also a tool for personal branding. To end, it is argued that different linguistic choices show signs of metapragmatic awareness with the politicians reflecting on the communicative practice in which they are involved, indicating that they creatively use this type of social media to render their campaign talk searchable and ‘followable’.